Digitalization, Internal Control, and Treasurer Competence Effects on Government Financial Reporting Quality through Leadership Commitment - Sulastri Sulastri; Noviarti Noviarti; Arifin Siagian Siagian; Yosi Stefhani (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to analyze the effects of digitalization, internal control systems, and treasurer competence on government financial reporting quality, with leadership commitment as a mediating variable. Research Methodology: This study was conducted at the Ministry of Marine Affairs and Fisheries using a quantitative explanatory approach. Data were collected through a survey questionnaire distributed to 210 respondents involved in financial management. The analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. Results: The findings indicate that digitalization, internal control systems, and treasurer competence positively and significantly influence leadership commitment and the quality of government financial reporting. Among the predictors, internal control systems showed the strongest contribution to improving the reporting quality. Conclusions: The study concludes that Higher-quality government financial reporting can be achieved through the integration of digital systems, stronger internal control mechanisms, improved treasurer competence, and sustained leadership commitment. Leadership commitment strengthens the effectiveness of organizational and technological factors in enhancing the quality of financial reporting. Limitations: This study was limited to one central government institution and applied a cross-sectional survey design, which may reduce the generalizability of the findings to other public sector institutions. Contributions: This study contributes to the public sector accounting literature by integrating technological, organizational, and human resource perspectives into an empirical framework. The findings also have practical implications for policymakers and government institutions in improving financial governance, transparency, and accountability.